Advanced airway management for pre-hospital trauma patients. (April 2016) - Crewdson, Kate; Lockey, David
The need for timely and appropriate airway management for trauma patients is widely recognised. There are a small number of severely injured patients who cannot be adequately supported with basic airway manoeuvres, and require early advanced airway management. The way in which this care is provided remains highly controversial. Whilst it is clear that effective airway management remains a priority for all patients and poorly performed pre-hospital anaesthesia may be detrimental to patient outcome, debate remains over exactly which patients will benefit from early advanced airway interventions, and how it should be provided. The evidence base is small and inconsistent, with significant heterogeneity in the reported data, making it impossible to draw meaningful conclusions. Current practice is not standardised, and care is delivered by providers of different abilities using a range of equipment and techniques. Standards of care provided during in-hospital practice relating to these issues of provider competence, equipment, and monitoring should be directly translated into delivery of care outside the hospital, but this is not always the case. The aim of this review is to evaluate the current evidence surrounding pre-hospital advanced airway management.